Penerapan Konsep Desain Eksklusif sebagai Strategi Pemasaran Produk Kaos Nyenyes Palembang - Winda Agustina Saputri (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
The importance of design innovation amid fierce competition among local products, such as unique designs that combine modern styles and cultural elements, can attract consumers' attention. One local product that applies this concept is Kaos Nyenyes Palembang. This study aims to determine the application of the exclusive design concept as a marketing strategy for Kaos Nyenyes Palembang products. This qualitative study uses a literature review method. The results show that Kaos Nyenyes implements a “one color, one design” strategy with limited production to create scarcity value and designs that combine Palembang cultural elements such as songket motifs, the Ampera Bridge icon, and the Palembang language with a modern look. This strategy is effective in expanding the market and plays a role in preserving and introducing Palembang culture to the wider community